2021
DOI: 10.1097/sle.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 601 Colorectal Endoscopic Submucosal Dissections in a Single Western Center: Is Right Colon Location Still a Major Concern?

Abstract: Background: Endoscopic submucosal dissection (ESD), as a minimally invasive procedure for removal of early gastrointestinal neoplasms, is a standard approach in Asian countries. Outcomes of ESD in Western European countries significantly differ, which makes it more difficult to apply this procedure to daily-basis clinical routine. The aim of this study is to analyze the safety and efficiency of colorectal ESD based on a large series of cases performed by a single operator after finishing the learning curve per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
(43 reference statements)
3
9
0
Order By: Relevance
“…105 minutes, with a median lesion size of 26 mm in 2011 [29]. Another recent study in a western country showed a median time of 82.7 minutes for ESD, with a median lesion diameter of 44.3 mm [30]. This study's average ESD procedure time was 51.9 minutes, with a median size of 7.83 cm 2 , consistent with the study in a Northeast Asian country.…”
Section: Plos Onesupporting
confidence: 87%
“…105 minutes, with a median lesion size of 26 mm in 2011 [29]. Another recent study in a western country showed a median time of 82.7 minutes for ESD, with a median lesion diameter of 44.3 mm [30]. This study's average ESD procedure time was 51.9 minutes, with a median size of 7.83 cm 2 , consistent with the study in a Northeast Asian country.…”
Section: Plos Onesupporting
confidence: 87%
“…[28] Another recent study in western country showed median time of 82.7 minutes for ESD with median lesion diameter of 44.3 mm. [29] Our average ESD procedure time was 51.9 minutes with median size of 7.83 cm 2 , which was more consistent with experience in country of Northeast Asia.…”
Section: Discussionsupporting
confidence: 84%
“…João Santos-Antunes (MD, MSc) 1,2 , Mathieu Pioche (MD, PhD) 3 , Felipe Ramos-Zabala (MD, PhD) 4 , Paolo Cecinato (MD) 5 , Francisco Gallego (MD) 6 , Pedro Barreiro (MD) 7,8 , Catarina Félix (MD), 7 Sandro Sferrazza (MD) 9 , Frieder Berr (MD) 10 , Andrej Wagner (MD) 10 , Arnaud Lemmers (MD, PhD) 11 , Mariana Figueiredo (MD) 11 , Eduardo Albéniz (MD) 12 , Hugo Uchima (MD) 13,14 , Ricardo Küttner-Magalhães (MD) 15 , Carlos Fernandes (MD) 16 , Rui Morais (MD) 1 , Sunil Gupta (MD) 17 , Daniel Martinho-Dias 18 (MD), Elisabete Rios (MD) 19 , Isabel Faria-Ramos (MD, PhD) 2 , Margarida Marques (MD) 1 , Michael J Bourke (MBBS) 17 , Guilherme Macedo (MD, PhD) 1 95% confidence intervals for bootstrapping analyses were 1.5-13.7% and 7.7-53.8% for NC-Lymph Score 0 and 1 respectively. For scores 2 and 3, 95% confidence intervals were 0-62.5% and 0-100% respectively due to the limited number of patients in these subgroups.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Even though the majority of colorectal lesions can still be managed by EMR [5], the role of ESD in this context has been growing in the West [6,7], particularly in lesions with higher risk of harboring malignancy, such as non-granular lateral spreading tumors (LSTs) [8] and large granular mixed-type LSTs [9,10], as well as all of those presenting other high-risk features upon endoscopic evaluation [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation